The Influence of Lifestyle, Brand Ambassador, and Electronic Word of Mouth on Consumer Purchase Decisions on Somethinc Products in The Special Region of Yogyakarta - Putry, Rizky Melyana; Gunawan, Hamzah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how lifestyle, brand ambassador, and electronic word of mouth on purchasing decisions for Somethinc products in Yogyakarta. Using questionnaires and the non-probability sampling approach, 100 respondents made up the study's sample. The research findings demonstrate that: (1) Lifestyle does not significantly impact the purchasing decisions for Somethinc products. (2) Brand ambassador positively and significantly impacts the purchasing decisions for Somethinc products. (3) Electronic word of mouth positively and significantly impacts the purchasing decisions for Somethinc products. (4) Lifestyle, brand ambassador, and electronic word of mouth collectively have a significant impact on the purchasing decisions for Somethinc products.